Eine semantische Analyse der Perfektivierungspraefigierung im Russischen. Fallstudie pere- - Demjjanow, Assinja (Slavistische Beitraege, 1998)
The work consists of two parts. The first part deals exclusively with the aspect properties of Russian prefigured verbs. A perfective analysis for Russian is proposed, which allows to grasp the semantic differences between imperfective Simplizia and its derivative derivatives in semantic terms. The second part of the thesis is an application of the proposed perfective analysis to Russian pere-prefixed verbs. It is shown that the meaning variants of pere-prefixed verbs in Russian can be derived from a general prefix scheme and the semantics of the stem verb.